2014
DOI: 10.1159/000365744
|View full text |Cite
|
Sign up to set email alerts
|

<b><i>Heme Oxygenase-1</i></b> Promoter Polymorphisms and Neonatal Jaundice

Abstract: Background: Heme oxygenase (HO) is the initial, rate-limiting enzyme in the conversion of heme to bilirubin. Dinucleotide (GT)n repeat length in the promoter region of the encoding gene modulates transcription: shorter alleles, in contrast with longer allele counterparts, are associated with greater gene expression and should result in increased heme catabolism. Objective: We compared the rates of heme catabolism and plasma total bilirubin (TB) between HO-1 promoter genotypes of varying (GT)n Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…9 Kaplan et al also showed that (GT)n repeat length did not regulate TB level in a population of Israeli neonates. 24 Both studies, however, categorized (GT)n repeat length into three classes and also used a higher cut-off number in their S classification (26 and 24, respectively) compared with that in the present study (<22). The present S classification is similar to that chosen by Tiwari et al (<21).…”
Section: Hyperbilirubinemicmentioning
confidence: 59%
“…9 Kaplan et al also showed that (GT)n repeat length did not regulate TB level in a population of Israeli neonates. 24 Both studies, however, categorized (GT)n repeat length into three classes and also used a higher cut-off number in their S classification (26 and 24, respectively) compared with that in the present study (<22). The present S classification is similar to that chosen by Tiwari et al (<21).…”
Section: Hyperbilirubinemicmentioning
confidence: 59%
“…6,24 For that reason, a group of researchers recently reanalyzed stored deoxyribonucleic acid for heme oxygenase-1 promoter variants from neonates enrolled in a previous study 25 with the implicit aim of identifying another mechanism for G6PD deficiency-associated hyperbilirubinemia. 26 The results from this post hoc study were negative, but the findings should be interpreted cautiously because of the small sample size as acknowledged by the authors. 26 The relationship between G6PD deficiency-associated hyperbilirubinemia and Gilbert syndrome is confounded by an observation that Gilbert syndrome itself may be associated with increased hemolysis.…”
Section: Prevalence Of Gilbert Syndrome Is Out Of Proportion With Thementioning
confidence: 72%
“…26 The results from this post hoc study were negative, but the findings should be interpreted cautiously because of the small sample size as acknowledged by the authors. 26 The relationship between G6PD deficiency-associated hyperbilirubinemia and Gilbert syndrome is confounded by an observation that Gilbert syndrome itself may be associated with increased hemolysis. 27 This observation is possibly due to that people with Gilbert syndrome may have increased hematocrit levels and hemoglobin levels as it has been shown in male adolescents and adults with Gilbert syndrome.…”
Section: Prevalence Of Gilbert Syndrome Is Out Of Proportion With Thementioning
confidence: 72%
“…In the human promoter region of the HO-1 gene, there is a polymorphic (GT)n repeat that regulates gene expression [23], with short (GT)n repeats associated with high HO-1 expression. In a cohort of infants from Israel, no association was observed between the rate of heme catabolism or plasma total bilirubin levels and HO-1 promoter genotypes in the steady state [24]. However, in a Japanese population of nonhemolytic term infants, we found that the presence of short (GT)n alleles was significantly higher in hyperbilirubinemic (18%) than in control neonates (7%) [25].…”
Section: Discussionmentioning
confidence: 99%